Weight Cycling in Women: Adaptation or Risk? - Carey, Katelyn J.; Vitek, Wendy (Seminars in Reproductive Medicine, 2020)
Obesity, dieting, and weight cycling are common among reproductive-age women. Weight cycling refers to intentional weight loss followed by unintentional weight regain. Weight loss is accompanied by changes in gut peptides, adipose hormones, and energy expenditure that promote weight regain to a tightly regulated set point. While weight loss can improve body composition and surrogate markers of cardiometabolic health, it is hypothesized that the weight regain can result in an overshoot effect, resulting in excess weight gain, altered body composition, and negative effects on surrogate markers of cardiometabolic health. Numerous observational studies have examined the association of weight cycling and health outcomes. There appears to be modest association between weight cycling with type 2 diabetes mellitus and dyslipidemia in women, but no association with hypertension, cardiovascular events, and overall cancer risk. Interestingly, mild weight cycling may be associated with a decreased risk of overall and cardiovascular mortality. Little is known about the effects of weight cycling in the preconception period. Although obesity and weight gain are associated with pregnancy complications, preconception weight loss does not appear to mitigate the risk of most pregnancy complications related to obesity. Research on preconception weight cycling may provide insight into this paradox.
Keywords: weight cycling; yo-yo dieting; women; reproductive outcome; diabetes